Expression Profiles of Long Noncoding and Messenger RNAs in Epicardial Adipose Tissue-Derived from Patients with Coronary Atherosclerosis - Du, Yu; Zhu, Yong; Liu, Yan; Liu, Jinxing; Hu, Chengping; Sun, Yan; Zhang, Dai; Lv, Sai; Cheng, Yujing; Han, Hongya; Zhang, Jianwei; Zhao, Yingxin; et al. (Current Vascular Pharmacology, 2022)
Background: Given its close anatomical location to the heart and its endocrine properties, attention on epicardial adipose tissue (EAT) has increased. Objective: This study investigated the expression profiles of long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs) in EAT derived from patients with coronary artery disease (CAD). Methods: EAT samples from 8 CAD, and 8 non-CAD patients were obtained during open-heart surgery, respectively. The expression of lncRNAs and mRNAs in each EAT sample was investigated using microarray analysis and further verified using reverse transcription-quantitative polymerase chain reaction. Results: Overall, 1,093 differentially expressed mRNAs and 2,282 differentially expressed lncRNAs were identified in EAT from CAD vs. non-CAD patients. Analysis using Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes showed that these differentially expressed genes were mainly enriched in various inflammatory, immune, and metabolic processes. They were also involved in osteoclast differentiation, B cell receptor and adipocytokine signaling, and insulin resistance pathways. Additionally, lncRNA-mRNA and lncRNA-target pathway networks were built to identify potential core genes (e.g., Lnc-CCDC68-2:1, AC010148.1, NONHSAT104810) involved in atherosclerotic pathogenesis. Conclusion: In summary, lncRNA and mRNA profiles in EAT were markedly different between CAD and non-CAD patients. Our study identifies several potential key genes and pathways that may participate in atherosclerosis development.
Keywords: messenger RNA